2010
DOI: 10.1089/ten.teb.2010.0176
|View full text |Cite
|
Sign up to set email alerts
|

Growth Factor Interactions in Bone Regeneration

Abstract: Bone regeneration is a complex process regulated by a large number of bioactive molecules. Many growth factors and cytokines involved in the natural process of bone healing have been identified and tested as potential therapeutic candidates to enhance the regeneration process. Although many of these studies show an enhancement of the bone regeneration process by a single drug therapy, in vivo bone regeneration is the result of a complex interplay between the applied growth factor and various endogenous produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
79
0
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(91 citation statements)
references
References 175 publications
(183 reference statements)
4
79
0
8
Order By: Relevance
“…21 For this reason, a number of investigators have explored the effects of the combined delivery of multiple growth factors. BMPs are well established as potent osteoinductive growth factors and their delivery in combination with other growth factors has been shown to enhance bone formation in vivo.…”
Section: Growth Factor Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…21 For this reason, a number of investigators have explored the effects of the combined delivery of multiple growth factors. BMPs are well established as potent osteoinductive growth factors and their delivery in combination with other growth factors has been shown to enhance bone formation in vivo.…”
Section: Growth Factor Deliverymentioning
confidence: 99%
“…BMPs are well established as potent osteoinductive growth factors and their delivery in combination with other growth factors has been shown to enhance bone formation in vivo. 21 A study by Duneas et al demonstrated that the combination of TGF-b and BMP-7 produced a synergistic effect to enhance bone formation in vivo. 22 This synergy was also observed by Simmons et al after they implanted RGD-modified alginate hydrogels containing both TGF-b3 and BMP-2 with bone marrow stromal cells (BMSCs) in mice.…”
Section: Growth Factor Deliverymentioning
confidence: 99%
“…1,2,[11][12][13] Growth factors are usually added to the system to strengthen MSC functionality. 14,15 Although embryonic stem (ES) cells have a much higher capacity to differentiate into many cell types, [16][17][18] there are several advantages to use MSCs rather than ES cells in addition to the ethical issues. First, ES cells have the potential to cause cancer such as teratoma, an encapsulated tumor with different organs such as hair, eye, teeth, and bone, and they are much more difficult to control in vivo than MSCs.…”
Section: Introductionmentioning
confidence: 99%
“…30 Given the importance of the angiogenesisosteogenesis coupling, combining the most important bioactive molecules involved in these processes can be beneficial for bone regeneration. 31 One of the major problems considering release of growth factors from delivery vehicles is the loss of biological activity. Since these growth factors have short biological half-lives, keeping the concentration of growth factor in the therapeutic window for a sufficient period of time is suggested to be important in mimicking natural bone regeneration.…”
Section: Introductionmentioning
confidence: 99%